DEMOKRASI DAN PERDA SYARIAT: KASUS SUKABUMI - FIRMAN NUGRAHA (Jurnal Dialog, 2017)
This article sheds some lights on the implementation of regional sharia regulations (Perda syariah) from the perspective of democracy, focusing on the aspects of representation and accountability. Qualitative study was employed in this research. The study finds out that the presence of regional sharia regulations in the context of democratic Sukabumi is substantially representative. This is due to the fact that Sukabumi people represent the majority group, which is Muslims. However, from the side of accountability, the regulations have low level of accountability since the sharia regulations have not solved the real issues amidst Sukabumi people. KEY WORDS: Accountability, Democracy, Regional Sharia Regulations, Reformation, Representative